FACTOR ASSOCIATED WITH CONTROL COMPLIANCE IN HYPERTENSION PATIENTS - Martono Martono; Rendi Editya Darmawan; Nur Hening Nita Purwitasari (Jurnal Ilmu Keperawatan Medikal Bedah, 2022)
Hypertension is a non-communicable disease that has a fairly high incidence. The World Health Organization (WHO) in 2019 reported 1.13 billion people in the world had hypertension. While the Basic Health Research (2018) reports that hypertension in Indonesia based on a doctor's diagnosis in the population shows that there are 63,309,620 Indonesians who suffer from hypertension. Hypertension is an important public health challenge in adulthood worldwide. However, in developing countries, appropriate treatment is often still not optimal. Adherence to antihypertensive medication can have a major effect on blood pressure control. The purpose of this study was to determine the factors associated with adherence to hypertension control. This research method uses correlational descriptive with a retrospective research design. Collecting data using secondary data from patient medical records with a sample of 201 respondents (purposive sampling). The analysis technique used binary logistic regression test at a 95% confidence level. Factors related to hypertension control compliance are age (2.4%), education (3.5%), occupation (11.7% contribution) and the most dominant factor related to hypertension control compliance is occupation with 11.7% contribution.